2012
DOI: 10.1039/c2cc31578e
|View full text |Cite
|
Sign up to set email alerts
|

nBu4NI-catalyzed C3-formylation of indoles with N-methylaniline

Abstract: nBu(4)NI-catalyzed C3-selective formylation of N-H and N-substituted indoles by using N-methylaniline as a formylating reagent was first successfully demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Yellow solid; yield 97%; mp 192–194 °C; 1 H-NMR (300 MHz, CDCl 3 + DMSO- d 6 ) δ 11.72 (s, 1H), 9.95 (bs, 1H), 8.59 (d, J = 1.8 Hz, 1H), 7.84 (d, J = 3.0 Hz, 1H), 7.53 (dd, J = 8.5, 1.8 Hz, 1H), 7.27 (d, J = 8.4 Hz, 1H) [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Yellow solid; yield 97%; mp 192–194 °C; 1 H-NMR (300 MHz, CDCl 3 + DMSO- d 6 ) δ 11.72 (s, 1H), 9.95 (bs, 1H), 8.59 (d, J = 1.8 Hz, 1H), 7.84 (d, J = 3.0 Hz, 1H), 7.53 (dd, J = 8.5, 1.8 Hz, 1H), 7.27 (d, J = 8.4 Hz, 1H) [25]. …”
Section: Methodsmentioning
confidence: 99%
“…In 2012, aT BAI-catalyzed C3-formylation of indoles with Nmethylaniline as the formyl source was demonstrated by Wang and co-workers. [18] By utilizing tert-butyl peroxybenzoate (TBPB) as the oxidant, different 3-formylindolesw ere obtained in good yields. Mechanistic assumption showed that iodine not only served as ar adicali nitiatort od ecompose peroxide, but also acted as an effective oxidizer fort he generation of iminium ions (Scheme 7).…”
Section: Càcb Ond-formation Reactionsmentioning
confidence: 99%
“…With TBHP as the oxidant, as eries of benzylic esters could be synthesized in excellent yields [Eq. (18)]. N otably,t his strategy could be used for the modification of aseries of N-Boc-protected (Boc = tert-butyloxycarbonyl)a mino acids.…”
Section: Càobond-formation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Figure ) Consequently, much effort has focused on the synthesis of 3‐acylindoles. In the past few years, the direct 3‐acylation of indoles has been developed, and is well synthetic procedures of 3‐acylindoles . On the other hand, direct construction of the 3‐acylindole skeleton from acyclic precursors has also got considerable attention, and some significant approaches have been achieved, such as intramolecular cyclization of enaminones, direct intramolecular oxidative coupling or radical cyclization of aminoalkynes, Rh‐catalyzed annulation of N‐phenylamidines with α‐Cl ketones, Ru‐ or Rh‐catalyzed selective C‐H activation/annulation of imidamides and sulfoxonium ylides, iodine‐mediated tandem aza ‐michael addition/C‐H functionalization of aniline and α,β‐ynones, copper‐catalyzed cyclization of N ‐(2‐iodoaryl)enaminones, visible light induced intramolecular radical cyclization of N ‐[2‐(alkynyl)phenyl]trifluoroacetimidoyl chlorides, Pd‐catalyzed isocyanide insertion and oxypalladation of alkyne, visible‐light‐induced oxidant and metal‐free dehydrogenative cascade trifluoromethylation and oxidation of 1,6‐enynes with water, as well as palladium‐catalyzed cyclization reaction of N ‐( o ‐haloaryl)alkynylimines producing 2‐trifluoromethylindole derivatives .…”
Section: Introductionmentioning
confidence: 99%